Combination of iron-silicate adsorption and Thermosynechococcus sp. CL-1 cultivation for swine wastewater treatment, CO2 fixation, phycobiliproteins generation. (December 2021) - Narindri Rara Winayu, Birgitta; Chen, Da-Siou; Hsueh, Hsin-Ta; Lin, Hong-Ping; Chu, Hsin
Abstract: Implementation of photosynthetic microorganism, like Thermosynechococcus sp. CL-1 (TCL-1), is considered as an eco-friendly strategy for carbon dioxide fixation and nutrient utilization in wastewater. However, high level of ammoniacal nitrogen carries out toxicity to TCL-1 cell and adsorption can be applied as a pre-treatment stage. This study observed application of iron-silicate on ammoniacal nitrogen adsorption in non-sterilized and undiluted swine wastewater as pre-treatment for TCL-1 cultivation for CO2 fixation, NH4 + -N degradation, and phycobiliprotein generation. The utilization of 100 g/L iron-silicate performed efficient adsorption with the quantity of 4.05 mg-N/g-Fe/Si and fitted the pseudo-first-order adsorption with R 2 value of 0.993. The adsorption pre-treated swine wastewater was implemented as TCL-1 growth medium under the 1000 μE/m 2 /s light intensity for 12 h. The TCL-1 biomass growth, CO2 fixation, and NH4 + -N removal rate during cultivation period reached to 31.67 ± 1.25; 57.54 ± 6.09; and 6.05 ± 0.20 mg/L/h respectively. Phycobiliprotein as a byproduct was generated with the productivity of 13.9 mg/g/h. Thus, coupling iron-silicate for pre-treatment step of TCL-1 cultivation in swine wastewater is eco-friendly strategy to reduce water demand for dilution, ignite phycobiliprotein accumulation during the CO2 fixation and nutrient utilization process. Graphical abstract: Unlabelled Image Highlights: Fe/silicate is a potential strategy to reduce water demand for wastewater dilution. Fe/silicate adsorbed NH4 + -N with a capacity 4.05 mg-N/g adsorbent. TCL-1 has high endurance to undiluted and non-sterilized swine wastewater. TCL-1 biomass productivity with swine wastewater after adsorption was 31.7 mg/L/h. Phycobiliprotein production reached to 13.9 mg/g-biomass/h.